2020
DOI: 10.3390/polym12040893
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of PVA Fluorescent Gel and Luminescence of Europium Sensitized by Terbium (III)

Abstract: Polyvinyl alcohol (PVA) gel has a very wide range of applications in agriculture, military, industry, and other fields. As a widely used water-soluble polymer, PVA has good mechanical properties, excellent spinnability, good hydrophilicity, remarkable physical and chemical stability, good film formation, is non-polluting, and exhibits good natural degradation and biocompatibility. It is an ideal gel preparation material. Incorporation of rare-earth elements into PVA polymers can be used to prepare rare-earth l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The peaks observed at 1367 cm −1 and 900 cm −1 are due to the characteristic absorption peaks of –CH 3 [ 16 ] and the β-linked glucan structure [ 17 ]. The new vibration peaks appeared in the light conversion films at 810 cm −1 and 737 cm −1 , which correspond to the infrared characteristic peaks of Eu–O and Tb–O [ 18 ] indicating the formation of coordination structures. Table S1 (see Supplementary Materials) summarizes the positions and changes of some absorption peaks of the films.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks observed at 1367 cm −1 and 900 cm −1 are due to the characteristic absorption peaks of –CH 3 [ 16 ] and the β-linked glucan structure [ 17 ]. The new vibration peaks appeared in the light conversion films at 810 cm −1 and 737 cm −1 , which correspond to the infrared characteristic peaks of Eu–O and Tb–O [ 18 ] indicating the formation of coordination structures. Table S1 (see Supplementary Materials) summarizes the positions and changes of some absorption peaks of the films.…”
Section: Resultsmentioning
confidence: 99%
“…This excitation that also known as the "antenna effect" is possessed by coordination ligands which can transfer energy from the ligand to the metal center resulting in luminescence of lanthanide ions [9]. A large number of special ligands have been synthesized for sensitizing the luminescence of metals [10][11][12][13][14][15][16][17], in particular, europium [18][19][20]. Among them βdiketones are excellent chelating ligands used to sensitize the luminescence of the europium ion and have proven themselves well [10,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide ions are usually regarded as prior metal ions to make fluorescent materials with different colors because of their excellent coordination abilities and fluorescence properties. 3,16,17 d−f transition enables intense metal-center luminescence, particularly when incorporated with sensitizing ligands in the first coordination sphere. 18−22 Based on that, Weng et al 23 have reported a multistimuli responsive fluorescent hydrogel controlled by the dynamic coordination of Eu 3+ -iminodiacetate.…”
Section: ■ Introductionmentioning
confidence: 99%